PENGARUH KUALITAS PELAYANAN DAN LOKASI DALAM MENENTUKAN LOYALITAS KONSUMEN PADA TOKO SS ASEMBAGUS SITUBONDO DENGAN KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING - yulistiawati, Mita; Ediyanto, Ediyanto; Praja, Yudha (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Marketing is one of the most important factors in the company, so it can be said that marketing is the heart of the life of the company or it can be said that the survival of the company is in marketing activities. The purpose of this study is to determine the effect of service quality and location in determining consumer loyalty at the SS Asembagus Situbondo Store with purchase decisions as an Intervening Variable. The population in this study are all consumers who come to the SS store. The random sampling method (simple probability) pays attention to the strata in the population in this research. In taking this sample using a presentation level of 10%. Data analysis and hypothesis testing in this study used the Structural Equation Model-partial Least Square (PLS-SEM).The results of the direct influence hypothesis test using the Smart PLS 3.0 application, indicate that service quality has a significant positive effect on purchasing decisions, location has a significant positive effect on purchasing decisions, service quality has a significant positive effect on consumer loyalty, location has a significant positive effect on consumer loyalty, consumer loyalty has a significant positive effect significantly positive on the purchase decision.